Political Strategy of Islamophobia in Indonesia: From the Old Order to the Reform Era - Hidayaturrahman, Mohammad; Witro, Doli; Binti Rosli, Roslieza; Ubaid, Ahmad Hasan; Putu Sugiantiningsih, Anak Agung (Politicon : Jurnal Ilmu Politik, 2025)
This study aims to uncover the models and forms of Islamophobia practised by the political regime in power in Indonesia. This study also analyses why the government in power in Indonesia makes policies and takes actions that lead to Islamophobia. This article uses qualitative explanatory methods. The data sources come from in-depth interviews with various informants and data is also collected through a literature study by exploring relevant data from various sources that can be accessed online, including books, journals, websites, and news portals. This study found that the political motives and strategies of the ruling regime in making policies and taking actions were based on Islamophobia, namely by diminishing the political power of Islam in Indonesia and eliminating its influence, which could disrupt the continuity of the ruling regime, which is controlled by nationalist groups. That way, the government can maintain power and carry out its agendas.